INVESTIGATION OF THE STRENGTH OF BASALT COMPOSITE REINFORCED AND COMBINED REINFORCED CONCRETE STRUCTURES ON NORMAL AND SLOPE SECTIONS - Solijonov Foziljon Sodiqjon ugli (Journals Park Publishing, 2023)
This article describes the analysis of the results of the research conducted on the study of the work of composite reinforced elements, which are widely used in the restoration of concrete structures in the buildings and structures currently being built in the Republic of Uzbekistan and in foreign countries.
Keywords: composite, basalt, concrete, flexibility, strength, messura, polymer.